The Influence of Georgia's Quality Rated System on School Readiness in Pre-School Children - Dena Phillips; Nancy Webb (Georgia Southern University, 2016)
Background: Georgia rates the quality of early childcare learning centers using a tiered quality improvement system. Georgia's Quality Rated system (QR) designates a star level, (one star, two stars or three stars) to each center based on a portfolio of QR standards and an onsite assessment by Georgia Department of Early Care and Learning (DECAL). Childcare centers applying for QR status first submit a portfolio documenting how their practices align with QR standards centered on staff qualifications; child health, nutrition and physical activity; family engagement; holistic curricula and teacher-to-student ratios. Subsequently, an on-site assessment of the center is performed by DECAL using the Early Childhood Environment Rating Scale- Revised (ECERS-R). Methods: The Bracken School Readiness Assessment-3rd Edition (BSRA-3) was administered to children in various one-star (N=2), two-star (N=4) and three-star (N=6) childcare learning centers in Georgia. Children's height and weight were recorded and BMI assessments were conducted. Results: Significant differences were found in school readiness scores based on quality rating with two and three star centers scoring higher than one star centers. Children in childcare centers at the one-star level (Mean = 95.00, SD = 16.80) performed lower than children in childcare centers at the two-star level (Mean = 103.67, SD = 16.55) and three-star level (Mean = 100.42, SD = 14.35). Multiple comparison tests did not reveal differences between two-star and three-star level centers. Conclusions: Higher levels of quality in QR childcare centers displayed more school readiness than centers with lower levels of quality. Future studies should examine differences in higher quality centers to further explore the influence of QR programs on school readiness.